Factors that influence the piracy of digital music from the Internet in Chile - Uribe, Rodrigo; Martínez, Carolina (Estudios de Administración, 2009)
This study examines the factors are associated with music piracy on the web in a sample of university students. The Theory of Planed Behavior (attitude toward behavior, perceived behavioral control, morality, past behavior and subjective norms) and two demographic variables (sex and age) are used to determine what factors influencie the illegal download of file from the internet. Analyses demonstrate that this model has good predictive power to explain the intention to pirate (45% of the variance). Moreover, with the only exception of sex, all the variables have significant predictive power.